Understanding the Impact of Scale Height on the Kinetics and Kinematics of Dogs in Working Trials - Carter, Anne; Boyd, Jacqueline; Williams, Ellen (Frontiers in Veterinary Science, 2022)
Working trials is a canine discipline that originated from police and military dog work. One aspect of working trials competition is for a dog to ‘scale’ a 6ft high wooden wall. Concern has been raised in other canine disciplines that landing forces after traversing jumps may lead to soft tissue injuries. There is a paucity of research into the impact of scale height on peak vertical landing force (PVF) in dogs participating in working trials. The aim of this work was to determine whether an alteration in scale height impacts PVF and apparent joint angulation on landing. 21 dogs who regularly competed in working trials traversed the scale at three different heights; 6ft (full height), 5.5ft and 5ft. Changes in PVF, apparent carpal and shoulder joint angulation and duration of landing were analyzed using general linear mixed models. Dogs weighing >25kg had greater PVF at 6ft than at 5ft (p<0.05). There was no effect of scale height on PVF in dogs <25kg. Duration of landing was longer at 5ft than 5.5ft (p<0.001) and 6ft (p<0.001). Apparent carpus angle on landing was smaller at 6ft than 5ft (p<0.05) and 5.5ft (p<0.05) for dogs <25kg. Apparent carpus angle on landing did not differ at any height for dogs >25kg (p>0.05). Apparent shoulder angle was not affected by scale height for any dogs (p>0.05). There was considerable variation in the study population, but this research indicates that when the scale height was lowered to 5.5ft dogs had reduced PVF and less compressed joint angles on landing. When the scale height was lowered to 5ft they altered their traversing style and greater compression and increased PVF was seen. Evidence-based approaches to canine working trials are important to ensure minimum impacts on physical health and welfare of participating dogs, in terms of risk of injury in both competition and training. Based on these findings it is recommended that the maximum height of the scale is reviewed for training and competitive purposes, to ensure minimal impacts on the health of competing dogs, while maintaining the level of competitive challenge.